Ewing’s Sarcoma of Ilium, Presenting as Right Lower Quadrant Pain - Osama Saleh Alshaya; Munzir Izzeldin Abbasher; Mubashir Maqbool Wani (Case Reports in Orthopedics)
Ewing’s sarcoma is a highly malignant tumor of bone and is more common in children in the age group of 10 to 20 years. Sometimes the classic clinical and radiological presentation of Ewing’s sarcoma may not be the norm and patient may have an atypical presentation leading to diagnostic confusion. This situation is especially true for Ewing’s sarcoma involving iliac bone. We report a case of Ewing’s sarcoma involving the right ilium in a patient presenting with right lower quadrant pain and nonspecific radiological changes. To the best of our knowledge, this scenario has not been reported in literature. We recommend early magnetic resonance imaging and computed tomography to diagnose the disease early when there is slightest suspicion of the disease.